SYSTEMATIC REVIEW AND META ANALYSIS PENGARUH UMUR DAN STATUS EKONOMI LANSIA TERHADAP RISIKO ELDERLY ABUSE - Diyono Diyono; Budi Kristanto; Sri Aminingsih; Tunjung Sri Yulianti (KOSALA : Jurnal Ilmu Kesehatan, 2024)
Latar belakang: Jumlah kelompok usia lanjut (lansia) meningkat drastis seiring dengan peningkatan usia harapan hidup. Proyeksi jumlah lansia di Indonesia tahun 2035 mencapai 48,2 juta jiwa 15,77%, lebih tinggi dari angka global yaitu 28,8 juta (11,34%). Semakin lanjut usia individu akan diikuti dengan penurunan kemampuan fisik dan produktifitas sehingga sering menjadi beban keluarga. Tujuan penelitian ini untuk Mengidentifikasi pengaruh umur dan status ekonomi lansia terhadap risiko elderly abuse berdasar studi literatur. Metode Systematic Review dengan basis data Science Direct, Google schoolar, dan PubMed menggunakan program Harzing’s Publish or Peris.  Medical Subject Heading (Mesh) “risk factors” yang dikombinasikan dengan “Elderly Abuse” OR “elderly negelct” OR “elderly maltreatment”. Meta analisis menggunakan program MedCalc Statistic Seri 22. Hasil penelitian 1). Umur yang sangat lanjut meningkatkan terjadinya elderly abuse (OR=47,82; p:<0,001;CI: 11,804 to 14,577). 2) Status ekonomi lansia tidak meningkatkan risiko Elderly Abuse (p=0,436). Kesimpulan penelitian ini menunjukkan usia yang sangat lanjut meningkatkan risiko elderly abuse, sedangkan status ekonomi lansia tidak berpengaruh terhadap risiko elderly abuse.   Kata kunci: elderly abuse, elderly maltreatment, elderly neglect, status ekonomi, umur   Background: the number of elderly people (seniors) has increased drastically along with increasing life expectancy. The projected number of elderly people in Indonesia in 2035 will reach 48.2 million people, 15.77%, higher than the global figure of 28.8 million (11.34%). As individuals age, physical abilities and productivity decline, which often becomes a burden on the family. The aim of this research was to identifying the influence of age and economic status of the elderly on the risk of elderly abuse based on literature studies. Methods: Systematic Review with Science Direct, Google Scholar, and PubMed databases using the Harzing's Publish or Peris program. Medical Subject Heading (Mesh) “risk factors” combined with “Elderly Abuse” OR “elderly neglect” OR “elderly maltreatment”. Meta analysis using the MedCalc Statistics Series 22 program. The research results: 1). Very advanced age increases the occurrence of elderly abuse (OR=47.82; p:<0.001; CI: 11.804 to 14.577). 2) The economic status of the elderly does not increase the risk of Elderly Abuse (p=0.436). Conclusion: very advanced age increases the risk of elderly abuse, while the economic status of the elderly has no effect on the risk of elderly abuse.   Keywords: elderly abuse, elderly maltreatment, elderly neglect, economic status, age